How a thirty-year-old quantum tale of two photons became ghost imaging - Andrew Forbes; Fazilah Nothlawala (Communications Physics)
The term Ghost Imaging embeds the notion that images can be formed by photons that have not interacted directly with an object. The first demonstration of ghost imaging turns 30, and the rich physics contained therein remains inspiring, fuelling advances in computational imaging with classical light, and novel imaging modalities with quantum light.